Understanding women's empowerment / Nurul Hayani Abd Rahman and Zuraidah Mohamed Isa - Abd Rahman, Nurul Hayani; Mohamed Isa, Zuraidah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Empowerment can be defined as a process of increasing the ability of an individual or a group to make choices and turn those choices into decisions and desired results. Accordingly, empowerment is a process in which a person becomes an agent of change through a transfer from "I can't" to "I can." Numerous studies have discussed empowerment. For example, a study conducted by Stromquist (1995) discussed empowerment with both cognitive and psychological components. Stromquist's (2002) study stated that empowerment involves understanding oneself and reported on the importance of making choices and decisions in life that may go against cultural and social expectations. Thus, empowerment involves the process of improving the status and capabilities of individuals to enable them to lead their lives independently.